2017
DOI: 10.6023/cjoc201612037
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and α-Glycosidase Inhibitory Activity of Three Ascorbic Acid Glycosides

Abstract: 2-O-(β-D-Glucopyranosyl)-L-ascorbic acid, a natural β-glycoside with ascorbic acid moiety present in Lycium barbarum, and its two analogues were chemically synthesized. Their inhibitory effect on yeast α-glucosidase and α-amylase were investigated with commercially available acarbose as positive control. The biological assays demonstrated the distinct inhibitory effect of these compounds on α-glucosidase activity and weak inhibitory activity against pancreatic α-amylase. The kinetic study indicated that these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…In 2017, Ma et al. ( 2017 ) upgraded the preparation method of AA‐2βG. The synthetic pathway of AA‐2βG is shown in Scheme 1 .…”
Section: Deep Processing Of Goji Berry Fruit and Its By‐productsmentioning
confidence: 99%
“…In 2017, Ma et al. ( 2017 ) upgraded the preparation method of AA‐2βG. The synthetic pathway of AA‐2βG is shown in Scheme 1 .…”
Section: Deep Processing Of Goji Berry Fruit and Its By‐productsmentioning
confidence: 99%
“…We suggested that AA-2βG had been lost from domestic apples ( Malus x domestica ) through centuries of selective breeding (it is also possible that the high AA-2βG content of crab apple fruit is due to a mutation preventing the degradation of AA-2βG in the fruit back to ascorbate and glucose). AA-2βG has similar stability to AA-2αG, a synthetic AAG used in many cosmetic products for its superior stability to AA. AA-2βG has been shown to act as pro-vitamin C when ingested by rats and to have various valuable physiological functions, including the potential to act as an alpha-glucosidase inhibitor and modulating gut microbiota to palliate colitis in mice. …”
Section: Introductionmentioning
confidence: 99%